ІЄРАРХІЧНА СИСТЕМА БАГАТОКРИТЕРІАЛЬНОГО ОПТИМАЛЬНОГО КЕРУВАННЯ РЕЖИМАМИ ДУГОВИХ СТАЛЕПЛАВИЛЬНИХ ПЕЧЕЙ З НЕЧІТКОЮ АДАПТАЦІЄЮ - Лозинський , О.Ю.; Паранчук, Я.С. (Інститут електродинаміки НАН України, Київ, 2012)
A hierarchical structure of multicriterion optimal control of arc steel melting furnaces regimes based on complex performance criterion and model of adaptation of such control based on Juzzy logic output system are proposed. The model of optimal control synthesis for complex performance criterion was substantiated. Electrical characteristics of the system were calculated. They illustrate the effciency of complex influence of arc furnace external characteristic artificial modifications on the electric and technological efficiency. References 1, figures 1.